Lunasin's Mechanism as an Antioxidant and Hypocholesterolemic Agent - Santi Widiasari; Sabrina Hayati; May Valzon; Wahyu Ramadhan (International Journal Of Health Science, 2025)
Several ways that can help lower cholesterol levels in the blood include using drugs (pharmacotherapy) or by modifying lifestyle and consuming certain foods. One of them is lunasin. Lunasin is a peptide found in soybean plants and is a promising drug candidate because it has broad health effects such as antioxidant, anti-inflammatory, anti-cancer, and lowering blood cholesterol through various mechanisms. This paper aims to examine the role and mechanism of action of lunasin as an antioxidant and its ability to lower blood cholesterol levels due to the unique peptide structure of lunasin as well as the bioavailability of lunasin starting from degradation, absorption, translocation and distribution of lunasin to target organs or target tissues after oral administration . This paper also discusses soybean plants as the main source of lunasin and the optimal content of lunasin in soybeans.